Analysis of three methodologies to teach town planning - Hidalgo García, David; Santiago Zaragoza, Juan Manuel; Arco Díaz, Julián (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
Teaching methodologies of the subjects of architecture and urbanism have evolved in the late years along with the advances endorsed by specialists in pedagogy and psychology. The number of their followers is increasing. However, it is difficult to find, within these fields, studies that deepen taking into account the opinion of the agents that means the main role in these methodologies, i.e.: students and lecturers. The objective of this article is to know the opinion about the subject of Urban Development Project, lectured in the H.T.S. of Building Engineering of the University of Granada, using the three most important methodologies of university teaching: masterly lesson, flipped classroom and project-based learning. Later it should be related these data with the improvement of their competences through the results obtained through its evaluation.